Identification of nanoparticles and their localization in algal biofilm by 3D-imaging secondary ion mass spectrometry. Issue 6 (28th March 2019) - Benettoni, Pietro; Stryhanyuk, Hryhoriy; Wagner, Stephan; Kollmer, Felix; Moreno Osorio, Jairo H.; Schmidt, Matthias; Reemtsma, Thorsten; Richnow, Hans-Hermann
Abstract : ToF-SIMS boundaries were pushed to enhance lateral resolution and mass resolving power for chemical imaging of nanoparticles in biological systems. Abstract : Characterization of nanoparticle (NP) interaction with an organic host requires identification and localization of nano-sized phases via high-resolution 3D imaging. Simultaneous molecular and spatial resolution causes many analytical approaches to face inherent performance limits, but this challenge can be overcome with time-of-flight secondary ion mass spectrometry (ToF-SIMS). To implement ToF-SIMS analysis of complex organic systems, a careful sample preparation is required to ensure ultra-high vacuum compatibility and to preserve the native chemical composition and spatial arrangement. In this present study, we developed a new method for the deposition of NPs from suspensions employing a polymer-coated substrate to avoid NP aggregation and to eliminate dissolved contaminants. We achieved a lateral resolution of 108 nm simultaneously with a mass resolving power (MRP = M /Δ M ) above 5000 in delayed extraction mode. Optimized ToF-SIMS performance allowed for (i) 3D localization of TiO2 NPs in Chlorella vulgaris biofilm, (ii) precise isotope-pattern-based identification of TiO2 -related secondary ions and (iii) elucidation of their composition dependence on the nearest molecular surrounding of the NPs. The developed sample preparation method in combination with the high resolution 3D visualization of NPs in algal biofilm paves the way to study NP fate and localization in complex environments simultaneously.